Development and Evaluation of a Stable Topical Cream Formulated with Annona squamosa Seed Extract as a Natural Pediculosis Agent - Nur Khairi; Lukman Muslimin; Fhahri Mubarak; Maulita Indrisari; Fajriansyah Fajriansyah (Biology, Medicine, & Natural Product Chemistry, 2025)
Head lice infestation (Pediculosis capitis) remains a global public health concern, exacerbated by growing resistance to conventional pediculicides such as permethrin and malathion. This study aimed to evaluate the pediculicidal activity and formulation stability of a topical cream containing Annona squamosa (sugar apple or srikaya) seed extract as a natural alternative for treating pediculosis. The ethanolic extract of A. squamosa seeds was obtained through maceration, producing a 10.005% yield. Pediculicidal assays were conducted using various extract concentrations (5%, 7.5%, and 10%), followed by formulation of oil-in-water creams with extract concentrations of 7.5%, 10%, and 12.5%. Physical stability tests included assessments of viscosity, pH, spreadability, adhesion, and homogeneity. Results showed a dose–response relationship, with lice mortality increasing from 60% at 5% extract to 87% at 10%. Extract. The formulated creams demonstrated high efficacy—86% to 96% mortality—comparable to 1% permethrin. All formulations maintained acceptable physicochemical properties (pH 4.8–5.5, viscosity within 27,000–47,000 cps) and remained stable after accelerated storage. These findings indicate that A. squamosa seed extract is a potent pediculicidal agent that can be effectively incorporated into a stable topical formulation. The study supports the potential of A. squamosa as a safe, sustainable, and plant-based alternative for managing pediculosis while addressing the challenge of chemical resistance.